Biodynamic diagnostics of the explosive power of the lower extremities: A case study - Čoh, Milan; Žvan, Milan (Acta Universitatis Carolinae. Kinanthropologica, 2011)
In many sports, vertical and drop jumps are an important exercise resource in an athlete's power training. This study aimed to establish the main dynamic and kinematic parameters that generate the efficiency of countermovement jump and drop jump, and establish the EMG activation of leg and back muscles. In the experimental procedures, one elite athlete triple jumpers took part. M. gastrocnemius medialis is one of the most important muscles in the production of mechanical energy in the kinetic chain. This is a two-joint muscle and can transfer energy between its segments. One-joint muscles generate the initial mechanical energy for vertical jumps, whereas two-joint muscles control the intramuscular coordina- tion and the final vertical impulse. In a drop jump from 40 cm the ankle joint sustains the highest loading, followed by the knee joint and the hip joint. Based on this information the training process can be far more accurately programmed and controlled in terms of power.
Keywords: výskok; seskok; Psychomotor Performance; psychomotorický výkon; pohyb; Adult; dolní končetina; Biomechanical Phenomena; Muscle, Skeletal; Case-Control Studies; dospělí; EMG; Electromyography; dynamika a kinematické parametry pohybu; svalová síla; Lower Extremity; elektromyografie; kosterní svaly; Muscle Strength; biomechanika; lidé; ženské pohlaví; studie případů a kontrol; sportovní výkon; Humans; Movement; Female; Athletic Performance